Небезпеки новітніх шляхів передачі інформації - Оленич, П. С. (ХНУРЕ, 2020)
Information transfer is a very important part of the modern digital world. Therefore, it is necessary to choose the right tools and methods for this process. Today, there is a close competition between wired and wireless connection methods. Both technologies have its own advantages and pitfalls and deserve consideration.
Keywords: транспортування інформація; ІЕЕЕ 802.3ba; бездротовий спосіб передачі інформації